A study on tourists’ motivation of visiting Kuching city, Sarawak / Abdul Zaheed Hanafi Sapheri & Aminah Mohamad Jainal - Sapheri, Abdul Zaheed Hanafi; Jainal, Aminah Mohamad (Faculty of Hotel and Tourism, 2018)
The purpose of this study is to investigate the factor in choosing Kuching tourism destination, tourist expectation towards tourism attraction in Kuching and overall satisfaction during their stay in Kuching. It also aims to investigate on how tourist socio-demographic characteristics affect their perception for the of satisfactions toward tourism attraction in Kuching city and result in tourist revisit. For the design and methodology approach, this study uses primary data and quantitative data. Distributed the questionnaire among the tourist visit Kuching to collect the data. Using SPSS to analyze the data. The frequency distribution and descriptive analysis is used to analyse and interpret the data. For the findings, the results of tourist motivation, tourist perception, and tourist satisfaction acomplished the research question and research objective. The overall result measure the level of tourists satisfaction towards Kuching city.